Effects of Water Availability on Leaf Trichome Density and Plant Growth and Development of Shepherdia ×utahensis - Chen, Ji-Jhong; Sun, Youping; Kopp, Kelly; Oki, Lorence; Jones, Scott B.; Hipps, Lawrence (Frontiers in Plant Science, 2022)
Approximately 65% of Utah’s culinary water is used for landscape irrigation, necessitating the establishment of landscapes using drought-tolerant plants that conserve water. Shepherdia ×utahensis (hybrid buffaloberry) is a drought-tolerant plant with dense leaf trichomes (epidermal appendages) that may limit excessive water loss by transpiration. However, little is known about how S. ×utahensis regulates leaf heat balance when transpirational cooling is limited. The objective of this research was to investigate the effects of substrate water availability on plant growth and development and trichome density of S. ×utahensis. Ninety-six clonally propagated plants were grown under an automated irrigation system, and their substrate volumetric water contents were controlled at 0.05 to 0.40 m3·m-3 for two months. Results showed that water stress impaired visual quality and plant growth. Shepherdia ×utahensis acclimates to drought by reducing cell dehydration and canopy overheating, which may be accomplished through decreased stomatal conductance, smaller leaf development, leaf curling, increased leaf thickness, and greater root to shoot ratio. Leaf trichome density increased when stem water potential (ψstem) decreased, resulting in greater leaf reflectance of visible light. Cell and leaf expansion were restricted under water stress due to low turgor pressure, and negative correlations were exhibited between epidermal cell size and trichome density. According to our results, plasticity in leaves and roots aids plants in tolerating abiotic stresses associated with drought. Acclimation of S. ×utahensis to water stress was associated with increased trichome density due to plasticity in cell size. Dense trichomes on leaves reflected more light which appeared to facilitate leaf temperature regulation.